Long-Term Disturbed Expression and DNA Methylation of SCAP/SREBP Signaling in the Mouse Lung From Assisted Reproductive Technologies - Le, Fang; Wang, Ning; Wang, Qijing; Yang, Xinyun; Li, Lejun; Wang, Liya; Liu, Xiaozhen; Hu, Minhao; Jin, Fan; Lou, Hangying (Frontiers in Genetics, 2021)
Assisted reproductive technology (ART) has been linked to cholesterol metabolic and respiratory disorders later in life, but the mechanisms by which biosynthetic signaling remain unclear. Lung inflammatory diseases are tightly linked with the sterol regulatory element-binding protein (SREBP) and SREBP cleavage-activating protein (SCAP), but this has not been shown in an ART offspring. Here, mouse models from a young to old age were established including in vitro fertilization (IVF), intracytoplasmic injection (ICSI), and in vivo fertilized groups. In our results, significantly higher plasma levels of CRP, IgM, and IgG were identified in the aged ICSI mice. Additionally, pulmonary inflammation was found in four aged ART mice. At three weeks, ART mice showed significantly downregulated levels of Scap, Srebp-1a, Srebp-1c, and Srebf2 mRNA in the lung. At the same time, significant differences in the DNA methylation rates of Scap-Srebfs and protein expression of nuclear forms of SREBPs (nSREBPs) were detected in the ART groups. Only abnormalities in the expression levels of Srebp-1a and Srebp-1c mRNA and nSREBP1 protein were found in the ART groups at 10 weeks. However, at 1.5 years old, aberrant expression levels and DNA methylation of SCAP, SREBP1, and SREBP2, and their associated target genes, were observed in the lung of the ART groups. Our results indicate that ART increases long-term alterations in SCAP/SREBP expression that may be associated with their aberrant methylation status in mouse.